Peningkatan Batas Aman Induksi Elektromagnetik Saluran Udara Tegangan Ekstra Tinggi (SUTET) 500 kV Bagi Kesehatan Manusia Berdasarkan Peraturan Menteri ESDM No. 18 Tahun 2015 Juncto No. 2 Tahun 2019 - Lolita Adhyana Joedo; Ivan Prasetyo Darmawan (Sekolah Tinggi Teknik - PLN, 2020)
The Development of Extra High Voltage (EHV) overhead power lines ( SUTET 500 kV) has become a national issue because based on several studies worldwide that shown residents who living next to power lines could increase the risk of their health problems. Therefore, there were huge protests from residents in Singosari and Gresik in 1991. The protest also happened in 2004, in which residents from Sumedang, Bogor, Cianjur, and Majalengka marching to Presidential Palace in Jakarta altogether. As a consequence, PLN and Faculty of Engineering of Gajah Mada University in 2005 developed collaborative research to identify HV and EHV required clearance of distance. This research refers to the WHO standard which determines the maximum of magnetic and electric field allowed, also refers to the Ministry of Mineral and Energy Resources Regulation No.01.P/47/M.PE/1992 which determines the minimum clearance distance between HV/ EVH bottom conductor with the ground as the safety levels concerning human exposure to electromagnetic fields. As the enactment regulation of the Ministry of Mineral and Energy Resources No. 18 of 2018 and its amendment No.2 of 2019, the regulation of HV, EHV, and also HVDC (High Voltage – Direct Current) free space and required clearance distance is determined. This research describes the comparison between PLN-UGM collaborative research with both Ministry regulation mentioned above.